MEDIASI KUALITAS LAYANAN: MENGUBAH NILAI RELASIONAL DAN NILAI SPIRITUAL MENJADI KEPUASAN ANGGOTA KSP CU BINA DANARTA - Susilowati, Elisabeth; Pawitan, Gandhi (Business Administration Department - Universitas Katolik Parahyangan, 2025)
This study aims to analyze the mediating role of service quality in the relationship between relational and spiritual values and member satisfaction in the mobile collection service of KSP CU Bina Danarta Palembang. This quantitative research employed a survey of 265 traditional market traders in Palembang (61.1% were females, aged 41-50 years). Primary data were collected through structured questionnaires using purposive sampling. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS to test causal and mediating effects. The results indicate that relational value and service quality have a positive and significant effect on satisfaction. However, a unique phenomenon of full mediation was identified: spiritual values (staff honesty and integrity) generate satisfaction only when manifested through professional, tangible service quality. For pragmatic market traders, physical evidence (tangibles) serves as the primary signal of security in transactions. The implications of this study are that management should modernize digital transaction tools and implement a standard Operating Procedure (SLA) to transform abstract values into measurable and credible service performance.